2015
DOI: 10.3390/ijms160612773
|View full text |Cite
|
Sign up to set email alerts
|

Families of microRNAs Expressed in Clusters Regulate Cell Signaling in Cervical Cancer

Abstract: Tumor cells have developed advantages to acquire hallmarks of cancer like apoptosis resistance, increased proliferation, migration, and invasion through cell signaling pathway misregulation. The sequential activation of genes in a pathway is regulated by miRNAs. Loss or gain of miRNA expression could activate or repress a particular cell axis. It is well known that aberrant miRNA expression is well recognized as an important step in the development of cancer. Individual miRNA expression is reported without con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 73 publications
(95 reference statements)
4
39
0
2
Order By: Relevance
“…In present study, we found that miR-106a was significantly upregulated in CC tissue samples and cell lines, which was consistent with previous microarray analyses data (30). Increased miR-106a expression was prominently associated with malignant clinicopathological features of CC patients, including lymph node metastasis, lymphovascular space invasion and advanced FIGO stage.…”
Section: Discussionsupporting
confidence: 80%
“…In present study, we found that miR-106a was significantly upregulated in CC tissue samples and cell lines, which was consistent with previous microarray analyses data (30). Increased miR-106a expression was prominently associated with malignant clinicopathological features of CC patients, including lymph node metastasis, lymphovascular space invasion and advanced FIGO stage.…”
Section: Discussionsupporting
confidence: 80%
“…Of interest, we observed some of the same miR clusters altered by HPV16 E6/E7 expression as in studies of cervical cancer (57). HPV16 E6/E7 modulates both tumor-suppressive and oncogenic miR clusters.…”
Section: Discussionsupporting
confidence: 56%
“…Upregulation of oncomiRs and downregulation of anti‐oncomiRs by miRNA clusters helps the cells to acquire cancer hallmarks. Downregulation of miR‐99 (a member of miR‐let‐7c/99a), miR‐99b/125a and miR‐100/let‐7a‐2 can induce Homeobox A cluster 1 (HOXA1) and tribbles pseudokinase 2 (TRIB2) expression leading to MAPK pathway activation via mitogen‐activated protein kinase kinase 1 (MEK1), facilitating proliferation, migration and invasion (Servín‐González et al, ). Similarly, overexpression of miR‐17/92 and miR‐106a/363, reported to target PTEN and activate PI3K, results in enhanced cell survival, proliferation, migration and invasion.…”
Section: Oncogenic and Tumour‐suppressor Mirna Clustersmentioning
confidence: 99%